Nine new species of Cnodalonini (Coleoptera: Tenebrionidae) from Hainan Island, with additional records of other Tenebrionidae - Ando, Kiyoshi; Yuan, Cai-Xia (Zootaxa, 2021)
Seven known species of Tenebrionidae are recorded from Hainan Island, of which six species are recorded from this island for the first time. Also nine new species of Cnodalonini are described from Hainan Is. under the names of Androsus pullus sp. n., Euhemicera hirtipes sp. n., Gnesis amabilis sp. n., Hemicera (Hemicera) viridula sp. n., Plamius laoshei sp. n., Pseudonautes fulgidicollis sp. n., Taichius caeruleopunctatus sp. n., Tetragonomenes sylvestris sp. n. and Tetraphyllus hlaicolus sp. n.